Living Skin - Saleh, Fawzi (Egypt; AlBatrik Art Production, 2010)
The film follows children working in a leather tannery in Cairo as it discovers the inhuman conditions which the people who live and work in the tanneries have to endure, surrounded by very dangerous chemicals, harmful to man and the environment.
Verzio Film Festival Submission
Keywords: Documentary films